Description of Information Needs in Cervical Cancer Patients - Ayuni, Putri; Deli, Hellena; Arneliwati, Arneliwati (CV. Rayyan Dwi Bharata, 2024)
The large number of cancer cases has led to the development of the science of cancer treatment, thereby increasing the need for information about the disease to prepare for the future. The aim of the research was to determine the information needs of cervical cancer patients at Arifin Achmad Regional Hospital. This research is quantitative research with descriptive methods. The sample for this study was 66 cervical cancer patients who were selected using a purposive sampling teachniques. Researchers used an information needs questionnaire that had been modified and tasted for validity. Data analysis in this study used univariate analysis. The research results showed that there were three types of information that were needed a lot by cervical cencer patients, namely information about prognosis 63 respondents (95.5%), prevention of spread 60 respondents (90.9%) and treatment 60 respondents (90.9%), and information that the majority did not need was information about alternative medicine 51 respondents (77.3%) and information about medical payments 43 respondnts (65.2%). Patients newly diagnosed with cervical cancer require extensive information about their disease, so it is recommended that health workers provide information according to the patient’s needs.